Emprego de um modelo de dispersão turbulento no estudo da universalidade da taxa de dissipação da energia - Gonçalves, Juliana Bittencourt (2010)
This study employed different autocorrelation functions and Maclaurin series expansions in the derivation of expressions describing the dissipation rate of turbulent kinetic energy. These expressions have the same functional form, but are described in terms of different numerical coefficients. The values obtained for the numerical coefficients were used in a Lagrangian stochastic dispersion model to simulate the dispersion of contaminants in the Planetary Boundary Layer (PBL). The simulation results were compared with concentration data observed in the Copenhagen experiment. The good performance of the parameterization and analysis through statistical indices showed that the mathematical relationships that describe the turbulent dissipation rate present an uncertainty. The analysis developed in this study indicates that there is no a universal functional form describing the dissipation rate of turbulent energy.